2022
DOI: 10.3390/ijms23052700
|View full text |Cite
|
Sign up to set email alerts
|

Replication-Deficient Lymphocytic Choriomeningitis Virus-Vectored Vaccine Candidate for the Induction of T Cell Immunity against Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis (Mtb) represents a major burden to global health, and refined vaccines are needed. Replication-deficient lymphocytic choriomeningitis virus (rLCMV)-based vaccine vectors against cytomegalovirus have proven safe for human use and elicited robust T cell responses in a large proportion of vaccine recipients. Here, we developed an rLCMV vaccine expressing the Mtb antigens TB10.4 and Ag85B. In mice, rLCMV elicited high frequencies of polyfunctional Mtb-specific CD8 and CD4 T cell response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…CD8 + but not CD4 + T cells were efficiently boosted upon vector revaccination. According to this research, rLCMV may be helpful for adult and/or neonatal vaccination programs against pulmonary TB [79].…”
Section: Tb/flu-04lmentioning
confidence: 85%
“…CD8 + but not CD4 + T cells were efficiently boosted upon vector revaccination. According to this research, rLCMV may be helpful for adult and/or neonatal vaccination programs against pulmonary TB [79].…”
Section: Tb/flu-04lmentioning
confidence: 85%
“…Due to their high immunogenicity, LCMV vectors have been explored as vaccine candidates for various diseases (8)(9)(10). In these prior studies, LCMV vectors have been genetically modified to include a foreign antigen to prime antigen-specific immune responses.…”
Section: Lcmv Vectorsmentioning
confidence: 99%
“…The replication-deficient lymphocytic choriomeningitis virus (rLCMV)-based vaccine vector expressing M.tb antigens Ag85B and TB10.4 (Ag85B-TB10.4) was tested in neonatal and adult mice. It was observed that after administration, this vaccine was capable of generating heterogeneous CD4 + , CD8 + T cell populations, and lung damage was reduced when infected with M.tb [ 26 ]. rLCMV may be developed as a novel vector for delivering mycobacterial antigens.…”
Section: Description Of Various Vaccine Candidates Designed Against Tbmentioning
confidence: 99%